Occupational burnout among obstetrics and gynaecology residents: a systematic review - Szcześniewska, Sylwia; Zaręba, Kornelia; Zgliczyński, Wojciech Stefan; Ciebiera, Michał; Feduniw, Stepan (Frontiers in Public Health, 2025)
IntroductionOccupational burnout, a complex condition frequently affecting highly committed individuals, is characterized by persistent emotional, mental, and physical exhaustion. The demanding nature of specialization in obstetrics and gynaecology makes residents particularly vulnerable to burnout. This study aimed to evaluate the mental and emotional well-being of residents during their specialization in obstetrics and gynaecology, as well as their susceptibility to stressors and the resulting burnout.Materials and methodsA systematic literature review was conducted in accordance with PRISMA guidelines. The PubMed, Web of Science, and Cochrane Library databases were searched to identify peer-reviewed articles examining the mental and emotional well-being of physicians during their residency in obstetrics and gynaecology their exposure to stressors and associated risk of burnout. Studies published before 30 August 2024 were included in the review.ResultsA total of 16 studies were analysed, revealing that the prevalence of burnout among obstetrics and gynaecology residents ranges from 46 to 86%. The studies indicate that residency in obstetrics and gynaecology significantly increases the risk of burnout, driven by factors such as psychological stress, young age, long working hours, female gender, and lack of support.ConclusionThe persistently high incidence of burnout among obstetrics and gynaecology residents underscores the urgent need for targeted preventive measures and enhanced mental health support within this field. Immediate action is required to address these issues by challenging stigma, reforming residency structures, improving both workplace and personal environments, and implementing comprehensive strategies to support residents’ mental well-being, with particular attention to emotional exhaustion, depression, and suicidal ideation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251067594, identifier CRD420251067594.